Penyuluhan dan Pelatihan Cara Mendapatkan Pinjaman Kredit dari Bank Kepada Pelaku Wirausaha di Destinasi Wisata Danau Cipondoh, Banten - Heny Ratnanningtyas; Nurbaeti Nurbaeti; Anita Swantari (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
This community service aims to provide socialization on how to get loans from banks for entrepreneurs in Lake Cipondoh who have businesses in these tourist attractions. Through this activity, entrepreneurs in Lake Cipondoh are motivated to borrow funds from financial institutions, namely banks, not moneylenders. This activity involved 27 entrepreneurs, this activity was carried out using counseling, training and consultation methods. This activity includes how entrepreneurs can easily borrow bank credit, easy steps for entrepreneurs to get business capital from banks and how to make proposals. The results of the training activities show that entrepreneurs know more about how to get credit loans from banks so that by seeking business capital from banks, they will get an injection of fresh funds, which can make businesses develop faster and faster.